COMMUNITY PARTICIPATION IN EDUCATION MANAGEMENT FOR IMPROVING QUALITY EDUCATION - Zaenal Arifin (DIA: Jurnal Administrasi Publik, 2016)
This research deeply discusses about implementation of community participation in the education management in Primary Shool (SD) and Islamic Primary Shool (MI) in Sidoarjo District, in East Java especially related to the participation processes, forms or models, levels or strata and functions,Â  the obstacles or problems and the supports factors, and how to overcome all problems, and to find alternative participation implementation models. Moreover, this researchÂ  followsÂ  Moeover, this research infolved School Commite, Head Master, and Community leader in 18 Sub Distrcts in Sidoarjo District of East Java Indonesia. The conclusion and suggestions, of the research can be seen as follow : Community Participation in Edication ManagementÂ  has functions as : (1) Community fund rising; (2)Â  the improvement of community attention and commitment; (3) the improvement of parent and community participation to make a better quality of education; and (4) the evaluation and supervision of education policy and the product of education. The opstacles of the community participation in education management are : (1) In Planning; (2) In Organizing and implementing; and (3) In monitoring and evaluation. The supporting factors are : (1) In planning and monitoring by using School Website; (2) BOS/BOSDA (School Operatinal Fund) very helpful for the poor parents to reduce the school payment; (3) Teacher Sertification Programe give positif impact to increase the spirit of teaching and learning process in the shool. Suggestions/Recommendations are : (1) School Commity needs reposition; (2) School need democracy improvement; (3) School needs improvement of tranparancy, acuntability, and responsiveness; (4) School needs improvement of cooperation with Higher Education; (5) District Government should give Recommendation Easily for the CSR (Corporate Social Responsibility) programe; (6) School Commity needsÂ Â  support from everybody to the positif effort for better quality of education; (7) To know deeperÂ  about the positive impacts of WebsiteÂ  or the development of Information, Communication, and Technology (ICT) in Education Management, needs further and deeper research mus be done. Key words : â€œCommunity Participationâ€.